Memory T cell responses targeting the SARS coronavirus persist up to 11 years post-infection. Issue 17 (12th April 2016) - Ng, Oi-Wing; Chia, Adeline; Tan, Anthony T.; Jadi, Ramesh S.; Leong, Hoe Nam; Bertoletti, Antonio; Tan, Yee-Joo
Abstract: Severe acute respiratory syndrome (SARS) is a highly contagious infectious disease which first emerged in late 2002, caused by a then novel human coronavirus, SARS coronavirus (SARS-CoV). The virus is believed to have originated from bats and transmitted to human through intermediate animals such as civet cats. The re-emergence of SARS-CoV remains a valid concern due to the continual persistence of zoonotic SARS-CoVs and SARS-like CoVs (SL-CoVs) in bat reservoirs. In this study, the screening for the presence of SARS-specific T cells in a cohort of three SARS-recovered individuals at 9 and 11 years post-infection was carried out, and all memory T cell responses detected target the SARS-CoV structural proteins. Two CD8 + T cell responses targeting the SARS-CoV membrane (M) and nucleocapsid (N) proteins were characterized by determining their HLA restriction and minimal T cell epitope regions. Furthermore, these responses were found to persist up to 11 years post-infection. An absence of cross-reactivity of these CD8 + T cell responses against the newly-emerged Middle East respiratory syndrome coronavirus (MERS-CoV) was also demonstrated. The knowledge of the persistence of SARS-specific celullar immunity targeting the viral structural proteins in SARS-recovered individuals is important in the design and development of SARS vaccines, which are currently unavailable.